Implementasi Kepemimpinan Kearifan Lokal Bugis pada Manajemen Berbasis Sekolah di Kabupaten Bone - Dwiyama, Fajri (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2024)
This study examines the implementation of Bugis local wisdom leadership values in the context of school-based management (SBM) in Bone Regency, South Sulawesi. The local wisdom of Bugis which is reflected in the concept of "pappaseng" and leadership values such as "lempu" (honesty), "acca" (intelligence), "sitinaja" (propriety), "getteng" (constancy), and "reso" (hard work) are the focus of this research. Through a qualitative approach with a case study method, this study reveals how these values are integrated in school leadership practices and their influence on the effectiveness of SBM implementation. The results of the study show that the application of Bugis local wisdom values in school leadership contributes positively to more effective school management, increased community participation, and strengthening the character of students.